Dark Patterns and Consumer Welfare in Digital Banking Practices in Southeast Asia: A Study of Indonesia, Malaysia, and Vietnam - Agustianto Agustianto; Nurlaily Nurlaily; Lu Sudirman; Nur Fatihah; Hari Sutra Disemadi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
Consumer welfare in digital banking environment has become increasingly important, as dark patterns have been observed to have continued to emerge in many digital spaces. This subtle yet dangerous modern iteration of old unethical trade practices presents a serious threat to growing economies like Indonesia, Malaysia, and Vietnam, that are increasingly reliant on digital banking services in daily life activities. This study employs the normative legal research method and comparative approach to assess the key legal implications of dark patterns on banking consumers’ welfare and how the existing relevant frameworks are responding to this significant threat. Analyses made throughout the study highlight that all three jurisdictions exhibit a bifurcated inadequacy where general consumer protection laws lack digital-specific application mechanisms, while banking regulations prioritize prudential soundness over interface-level manipulation. Despite the divergent nature of the gaps found, UI/UX interface regulation remains the biggest gap that all three countries are dealing with, which is the primary manifestation of dark patterns. The study recommends establishing mandatory interface design standards supervised by regulatory authorities capable of imposing ex ante structural obligations on banks, to ensure that consumer welfare remains the paramount importance in ever-so-essential digital banking services.